Pemberdayaan Koperasi untuk Edukasi Pengelolaan Sampah: Mendorong Desa Ciburayut Menuju Kebersihan dan Kemandirian - Natadiharja, Sri Sukartono; Lukiyana, Lukiyana; Diansyah, Diansyah; Reza, Bobby; Nugroho, Prasetya Adi; Hidajat, Koerniawan; Putra, Robiur Rahmat (Jurnal Pemberdayaan Nusantara, 2025)
The increasing volume of household waste in rural areas has become a significant environmental challenge, requiring sustainable and community-based solutions. This Community Service Program (PKM) aims to empower local cooperatives as key agents in driving waste management education, fostering environmental awareness, and promoting sustainable livelihoods in Ciburayut Village, Cigombong District, Bogor Regency, West Java, Indonesia. The program adopts a participatory approach through capacity building, training, and collaborative action between cooperatives, local government, and community members. Activities include educational workshops on waste segregation, recycling practices, and the development of waste-based products to support the village economy. The results demonstrate improved community knowledge and behavior in waste handling, increased cooperative engagement in environmental initiatives, and the establishment of a waste management system that supports both cleanliness and economic independence. This initiative highlights the strategic role of cooperatives in integrating environmental education with economic empowerment, serving as a replicable model for other rural communities seeking sustainable development